Endoscopic ultrasound-guided radiofrequency ablation as therapeutic approach for pancreatic insulinoma - Darshini S; Khairul Najmi Muhammad Nawawi; Kok, WH; Lee, CC; Woo, WH; Wong, Z (Penerbit Universiti Kebangsaan Malaysia, 2024)
Insulinoma is one of the most prevalent form of functional neuroendocrine tumor of the pancreas (PNET) that often manifests with debilitating symptomatic hypoglycemia. When conventional imaging fails to detect the lesion, endoscopic ultrasound (EUS) have proven to be of value to determine the preoperative localisation as well as with biochemical sampling via fine needle aspiration of the suspected lesion. Surgical resection has been the standard care for these pancreatic neuroendocrine tumors. However, with recent advancements, endoscopic ultrasound-guided radiofrequency ablation (EUS-RFA) has emerged as a promising and less invasive therapeutic approach that carries a favourable outcome and a low risk of complications. We report eda patient with symptomatic pancreatic insulinoma who was treated with EUS-RFA.